Information Systems Protection in Financial Institutions - Onyshshenko, Svitlana; Sivitska, Svitlana; Shapovalova, Olena; Cherviak, Anna (International Journal of Engineering and Technology, 2018)
Information security is of great importance for the vital interests of any state. Creation of a developed and protected environment is an indispensable condition for the development of society and the state, which should be based on the latest automated technical means. Because for the prompt execution of transactions, all services may be carried out through the Internet.Every day, the most pressing problem is the protection of information. Because the different areas of our lives are computerized, they have a wider range of viruses and unauthorized penetration. In order to counter external attacks, it is necessary not only to have effective protection tools, but also to know their system of work, settings and weaknesses of operating systems.Knowledge of the basics of information security, the ability to effectively prevent the leakage of information is particularly valuable at present due to the fact that there is an acute shortage of skilled professionals in the market.The basic concepts, structure and features of information technologies functioning in financial institutions operating are investigated. Unauthorized access possible types analysis to the institution information carried out. Methods and mechanisms financial institution information systems effective protection analysis is carried out.Â Â Â